T-cell redirecting therapies in lung cancer - a comprehensive analysis of clinical trials - Jiahe Zhao; Ayrton Bangolo; Lili Zhang; Martin Gutierrez; Miguel Gonzalez-Velez (Frontiers in Immunology, 2026)
Lung cancer remains the leading cause of cancer-related mortality worldwide, and despite the transformative impact of immune checkpoint inhibitors (ICIs), primary and acquired resistance, limited efficacy in immune-cold tumors such as extensive-stage small cell lung cancer (ES-SCLC), and the absence of durable responses in a substantial proportion of patients define the unmet need that T cell-redirected therapies aim to address. These strategies engage, engineer, and deliver cytotoxic T cells against tumor cells independently of preexisting immunity, and this review provides a comprehensive overview of the four major modalities under clinical development in lung cancer: bispecific T cell engagers (BiTEs), tumor-infiltrating lymphocyte (TIL) therapy, chimeric antigen receptor T cell (CAR-T) therapy, and T cell receptor-engineered T cell (TCR-T) therapy. Among these, tarlatamab, a DLL3×CD3 BiTE, has achieved the most advanced clinical validation, receiving traditional FDA approval in November 2025 for second-line ES-SCLC following Phase 3 DeLLphi-304 data demonstrating superior overall survival versus chemotherapy (median 13.6 vs. 8.3 months; HR 0.60). TIL therapy is the leading adoptive cell approach in non-small cell lung cancer (NSCLC), with lifileucel demonstrating a 25.6% ORR in anti-PD-1-resistant disease and a 64.3% ORR when combined with pembrolizumab in ICI-naïve patients, though manufacturing complexity and cost constrain broad access. CAR-T and TCR-T therapies remain in early proof-of-concept phases, limited by the absence of uniformly expressed tumor-restricted surface antigens in NSCLC, MHC class I downregulation, and the sub-1% eligibility rates imposed by HLA restriction in TCR-T programs, while generating important engineering insights around genome editing, armored cytokine payloads, and neoantigen targeting strategies. Shared challenges across all modalities include antigen loss under therapeutic pressure, T cell exhaustion driven by the immunosuppressive lung tumor microenvironment, and the absence of prospectively validated predictive biomarkers for patient selection. Combination strategies pairing T cell-redirected therapies with ICIs, antibody-drug conjugates, and allogeneic or innate immune effectors represent the most promising path toward durable benefit. As the field advances toward Phase 3 trials, biomarker-selected patient populations, and scalable allogeneic manufacturing platforms, T cell-redirected therapy is positioned to extend the survival frontier for patients whose lung cancer has escaped existing treatments.